Enhancing Workplace Performance: The Impact Of Emotional Intelligence Training On Women Employees - Priya, V.J. Mohana; Jayakani, S. (Journal of Neonatal Surgery, 2025)
Emotional intelligence (EI) plays a crucial role in workplace success, especially for women employees navigating professional challenges. This study examines the impact of Emotional Intelligence Training Programs (EITP) on the development of EI among women employees across various sectors. A dataset of 500 women employees was analyzed using ANOVA and regression analysis to measure the effectiveness of the training programs. The findings indicate a significant improvement in EI components such as self-awareness, self-regulation, motivation, empathy, and social skills post-training. ANOVA results confirm a statistically significant difference in EI levels before and after training, while regression analysis highlights the key factors influencing EI growth. The study underscores the importance of structured EI training in fostering better workplace adaptability, leadership skills, and overall job satisfaction among women employees.